The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jobaz.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Current situation, genetic relationship and control measures of infectious bronchitis virus variants circulating in African regions

Abstract: Infectious bronchitis virus (IBV) is a major viral pathogen of commercial poultry, affecting chickens of all ages and causing major economic losses in poultry industry worldwide. Frequent points of mutations and recombination events in the S1 gene region, result in the emergence of new IBVs variants circulating in the form of several serotypes/genotypes that can be partially or poorly neutralized by current vaccines. IBV is well studied worldwide, nevertheless in African countries epidemiological and scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…QX like IBV strains) and Mass type IBV isolates recovered from various geographical areas [18,42,43,45,46]. Nephropathogenic QX-type strains are distantly related to the M41 strain and their genetic similarity is 78.6% [60]. Based on the partial S1 sequence analysis of three nephropathogenic IBV isolates, which belong to the Mass genotype revealed that they are more than 99.1 and 97.8% identical to the classical M41 strain in nucleotide and deduced amino acid sequences, respectively [61].…”
Section: Discussionmentioning
confidence: 99%
“…QX like IBV strains) and Mass type IBV isolates recovered from various geographical areas [18,42,43,45,46]. Nephropathogenic QX-type strains are distantly related to the M41 strain and their genetic similarity is 78.6% [60]. Based on the partial S1 sequence analysis of three nephropathogenic IBV isolates, which belong to the Mass genotype revealed that they are more than 99.1 and 97.8% identical to the classical M41 strain in nucleotide and deduced amino acid sequences, respectively [61].…”
Section: Discussionmentioning
confidence: 99%
“…Effective vaccination against IBV is proving to be an increasing challenge due to the emergence of novel strains, such as QX, first isolated in China, in 1995 [ 29 ], and subsequently spread worldwide [ 30 , 31 , 32 ]. Whilst some strains of IBV have spread worldwide, others have emerged but remained limited to distinct geographical areas [ 33 , 34 ]. Commercial live IBV vaccines are generated through multiple passages of a pathogenic field isolate through embryonated hen’s eggs with the aim of generating a virus that is attenuated but still immunogenic [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is an enveloped positive-stranded RNA virus with a genome of about 27.6 kb in length encompassing 5 0 and 3 0 untranslated regions with a poly(A) tail. A major part of the genome is composed of two overlapping open reading frames (ORFs), 1a and 1b, which are translated into large polyproteins, 1a and 1ab, respectively, and contribute to the formation of the replication and transcription complex (Cavanagh., 1997;Khataby et al, 2016b). The remaining part of the genome encodes for four structural proteins that are called the phosphorylated nucleocapsid protein (N), the membrane glycoprotein (M), the envelope protein (E), and the spike glycoprotein (S).…”
Section: Introductionmentioning
confidence: 99%
“…The high variation in the nucleotide sequences of spike gene can change the protection ability of a vaccine or immunity (Cavanagh and Naqi, 2003). Some reports have demonstrated that this genetic diversity, due to changed genomic virus by frequent point mutations and recombination events in the S1 gene, has given the emergence of new IBV variants that can be partially or poorly neutralized by existing vaccine serotypes (Khataby et al, 2016b). Wherefore, the phylogenetic analysis of the S1 gene is the most useful strategy to differentiate IBV genotypes and serotypes, because it correlates closely with the serotype and permits the selection of the appropriate vaccine serotypes for IB control in each of the geographic regions (Jackwood, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation